Interaction of glyphosate with auxin herbicides for control of Benghal dayflower (Commelina benghalensis) at advanced growth stages - Willian F. Larini; Alfredo Junior P. Albrecht; Debora C. Neuberger; Arthur A.M. Barroso; Leandro P. Albrecht (Weed Technology)
Auxinic herbicides are the second most-used herbicides in Brazil, and are often combined with glyphosate in pre-plant burndowns management. However, efficacy of these herbicides against Benghal dayflower at advanced growth stages remains poorly understood. Two field experiments were conducted in 2021 and 2022 on no-till fields naturally infested with Benghal dayflower at an advanced growth stage (approximately 50 cm height, 100% soil coverage) to evaluated the control efficacy of 2,4-D at 966 g ae ha−1, triclopyr at 720 g ae ha−1, fluroxypyr at 400 g ae ha−1, and dicamba at 720 g ae ha−1, alone or in combination with glyphosate (1,550 g ae ha−1). Dicamba was also tested at rates from 288 to 1,008 g ae ha−1. Results indicate that Benghal dayflower exhibits variable responses to auxin herbicides, and is influenced by both chemical family and the herbicide molecule. None of the treatments provided complete control at 8 wk after application (WAA). The highest visible control (∼77%) and dry mass reduction (∼57%) were provided by triclopyr (applied alone or combined with glyphosate) and 2,4-D (combined with glyphosate), followed by fluroxypyr (alone or combined with glyphosate) and 2,4-D (alone), providing approximately 69% visible control and 54% dry mass reduction. Even when statistical differences were detected by adding glyphosate to auxin herbicides, these differences were not sufficient to characterize a synergistic effect or improve control consistency. Dicamba (isolated or combined with glyphosate) provided the lowest control (∼54%) and dry mass reduction (∼30%). Additionally, dicamba doses up to 1,008 g ae ha−1 did not provide complete control (∼60% visible control and 51% dry mass reduction), suggesting that dicamba limitations cannot be mitigated through a dose increase. By highlighting the challenges in controlling Benghal dayflower at advanced growth stages, these results emphasize the importance of early-stage weed control and the need to carefully assess which auxin herbicides to use and when glyphosate mixtures are necessary.